5 - Beyond Poverty: Why are Some Children more Vulnerable to Commercial Sexual Exploitation than Others? - Makaudze, Rejoice; Tofa, Eliot; Mushonga, Tichavona (Africa Development, 2024)
The commercial sexual exploitation of children (CSEC) is a conscience- wrenching problem that has become a pandemic feature of Zimbabwean society. Studies on CSEC have invested significant attention on identifying the factors that cause and perpetuate CSEC. There is a general consensus among studies that poverty is the main cause of CSEC. However, it is argued in this study that while the singular, dominant and generalised narrative that poverty is the main cause of CSEC is helpful, its deficiency is that it does not explain why some children are more vulnerable to CSEC than others. In order to address this question, this study examines how individual, family and societal risk factors cumulate in peculiar ways to make some children more vulnerable to CSE than others.